PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN SISWA MELALUI PENDIDIKAN AGAMA ISLAM PERSEPEKTIF THOMAS LICKONA DAN AL-GHAZALI - Khulashah Khulashah (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2023)
This study aims to explain the process of Islamic Religious Education which has a considerable role in shaping the financial aspects of students ' concern at the junior high school level to the environment. This is based on the current environment, has become a special concern of the world community. Starting from the problem of climate change, plastic waste to the energy crisis caused by humans themselves. This study uses qualitative methods of reference theory (refrence theory) against the thought of Thomas Lickona and Imam Al-Ghazali. The purpose of this study is to compare the theory of character education Thomas Lickona and Imam Al-Ghazali and the implementation process in SMPN 11 Jember. So that this study found the views of Thomas Lickona related to karaker education was dilandsi by three components namely moral knowledge, moral feelings and moral behavior. While al-Ghazali long before has offered moral education which is now termed with ecosufism, namely the relationship of values and morals such as reciprocity between humans, the universe and God. Implementation at SMPN 11 Jember has succeeded in forming a waste bank called the DASA JAKA program (from waste to Blessing) on november 7, 2022. This Program has been able to provide stimulation for students to practice the theory of environmental hygiene that has been taught by teachers. Penelitian ini bertujuan untuk menjelaskan proses pendidikan agama Islam yang memiliki peranan cukup fundmental dalam membentuk aspek kepedulian siswa pada tingkatan SMP terhadap lingkungan. Hal ini dilandasi lantaran lingkungan saat ini, telah menjadi perhatian khusus masyarakat dunia. Mulai dari problem perubahan iklim, sampah plastik hingga krisis energi yang diakibatkan manusia sendiri. Penelitian ini menggunakan metode kualitatif teori acuan (refrence theory) terhadap pemikiran Thomas Lickona dan Imam Al-Ghazali. Tujuan penelitian ini adalah mengkomparasikan atara teori pendidikan karakter Thomas Lickona dan Imam Al-Ghazali serta proses implementasinya di SMPN 11 Jember. Sehingga penelitian ini menemukan padangan Thomas Lickona terkait pendidikan karaker itu dilandsi oleh tiga komponen yakni pengetahuan moral, perasaan moral dan perilaku moral. Sedangkan al-Ghazali jauh sebelumnya telah menawarkan pendidikan akhlak yang sekarang diistilahkan dengan ekosufisme yakni relasi nilai dan moral betuk timbal balik antara manusia, alam semesta dan tuhan. Implementasi di SMPN 11 Jember telah berhasil membentuk bank sampah bernama program DASA JAKA (dari sampah menjadi berkah) pada 7 november 2022. Program ini telah mampu memberikan stimulasi bagi siswa untuk mempratekkan teori kebersihan lingkungan yang telah di ajarkan oleh guru.